قراءة في أبعاد الزمان في شعر أبي القاسم الشابي - سهل, ليلى (قــــــراءات; No 08 (2015): (مجلة قراءات( مارس, 2019)
تثير مقولة الزمن جدلا عميقا وممتدا باعتباره الوجه الآخر للكون وبوجود الإنسان في الكون بدأت الحياة البشرية مسيرة جريانها ، لهذا سنتناول بالدراسة أبعاد الزمان في شعر أبي القاسم الشابي، بداية بالماضي البعيد والتاريخ في شعره، مرورا بالزمن الحاضر والمعاصر، وصولا إلى توقف الزمن . The abstract :  Time expression launches a heated and extended profound debate by considering it the other side of universe. The life of the Human kind has started its journey, this study is devoted to tackle the subject matter of time dimension in the poetry of Abu Kassim Chabbi, starting by the mentioning of the ancient time and history in his poetry, passing to the present and post modern time, to reach the end of the time in his poetry.